The Effect of Giving Mung Bean Extract Onblood Pressure in Hypertension Patients at The Sri Rezeki Elderly Health Care Posyandu in Mojokrapak Village, Tambelang District, Jombang Regency - Maulidhea Maulidhea (Journal of Biotropical Research and Nature Technology, 2025)
High blood pressure, also known as hypertension, is a chronic condition in which blood flow in the arteries experiences excessive and often uncontrolled increases. Hypertension occurs due to the impact of several risk factors. Risk factors for hypertension include a family/genetic history of hypertension, advanced age, gender, diet, unhealthy diet, obesity, frequent smoking and alcohol consumption, stress, and lack of physical activity, which are the main risk factors for developing hypertension. Hypertension treatment includes not only pharmacological but also non-pharmacological methods. Providing green bean juice, rich in potassium and isoflavones, is an alternative for lowering blood pressure. Objective: At the Sri Rezeki Elderly Community Health Post (Posyandu Lansia Sri Rezeki), Mojokrapak Village, Tambelang District, Jombang Regency, this research aims to reveal the relationship between green bean juice consumption and changes in blood pressure in elderly individuals with hypertension. This study employed a comparative experimental design with a pretest-posttest model in two groups. The study population consisted of 80 elderly individuals, with a purposive sampling technique used to select 16 respondents. Information was obtained through recording on the observation sheet and checking blood circulation pressure with a sphygmomanometer, then analyzed using the paired T-test method. The study output showed that before being given the mung bean juice intervention there were 11 respondents with severe hypertension, while after the intervention a number of 6 respondents suffered from pre-hypertension. In the statistical analysis using the paired t-test method, the p value was obtained in line with 0.000 which was lower than the significance limit of 0.05. This output confirms that the consumption of mung bean juice plays an important role in lowering blood circulation pressure in the group of elderly people with hypertension who participated in Posyandu services in Mojokrapak Village, Tambelang District, Jombang Regency. Mung bean extract has been proven to be able to provide a positive effect in lowering blood circulation pressure in elderly people with hypertension, especially in individuals who are not disciplined in taking antihypertensive drugs and have an unbalanced diet.